Noninvasive Nuclear SPECT Myocardial Blood Flow Quantitation to Guide Management for Coronary Artery Disease. (September 2017) - Chen, Lung-Ching; Jong, Bor-Hsin; Lin, Sheng-Che; Ku, Chi-Tai; Chen, Ing-Jou; Chen, Yen-Kung; Hsu, Bailing
Abstract : Abstract: Recently, myocardial blood flow quantitation with dynamic SPECT has been validated to enhance the detection of multivessel coronary artery disease (CAD) and conclude equivocal SPECT myocardial perfusion study. This advance opened an important clinical application to utilize the tool in guiding CAD management for area where myocardial perfusion tracers for PET are unavailable or unaffordable. We present a clinical patient with ongoing recursive angina who underwent multiple nuclear stress tests for a sequence of CAD evaluation in 26 months and demonstrated that SPECT myocardial blood flow quantitation properly guided CAD management to warrant patient outcome.